From the limit definition of the derivative:
f ′ ( x ) = lim h → 0 f ( x + h ) − f ( x ) h g ′ ( x ) = lim h → 0 g ( x + h ) − g ( x ) h {\displaystyle \begin{align} &f'(x)=\lim_{h\to0}\frac{f(x+h)-f(x)}{h}\\ &g'(x)=\lim_{h\to0}\frac{g(x+h)-g(x)}{h} \end{align}}
d d x ( f ( x ) + g ( x ) ) = lim h → 0 f ( x + h ) + g ( x + h ) − f ( x ) − g ( x ) h = lim h → 0 f ( x + h ) − f ( x ) h + lim h → 0 g ( x + h ) − g ( x ) h = f ′ ( x ) + g ′ ( x ) {\displaystyle \begin{align} \frac{d}{dx}\bigl(f(x)+g(x)\bigr)&=\lim_{h\to0}\frac{f(x+h)+g(x+h)-f(x)-g(x)}{h}\\ &=\lim_{h\to0}\frac{f(x+h)-f(x)}{h}+\lim_{h\to0}\frac{g(x+h)-g(x)}{h}\\ &=f'(x)+g'(x)\end{align}}